New life, new feelings of loss: Journaling new motherhood during Covid-19 - Alice Larotonda; Katherine A. Mason (Elsevier, 2022)
In this article we analyze the longitudinal journals of 32 Pandemic Journaling Project (PJP) participants who were pregnant, planned a pregnancy, or gave birth between January 2020 and July 2021. Employing a grounded theory approach, we coded journals in NVivo for emerging themes related to the influence of the Covid-19 pandemic on perinatal experiences in North America and Europe. In the paper we first provide some brief background on perinatal mental health and on the particular conditions for pregnancy and birth during Covid-19, before introducing major themes that emerged from the data, along with three in-depth case studies. We argue that the new mothers and prospective mothers in our sample associated new life with new feelings of loss during Covid-19. New motherhood during Covid-19 has meant for PJP participants a loss of seemingly irretrievable opportunities and moments that they see as necessary for establishing themselves as mothers and integrating their babies into their families through a process of "kinning" (Howell, 2003). Feelings of loss associated with disruptions to kinning may be partially responsible for the increase in perinatal mental distress observed during the pandemic.